2022
DOI: 10.1088/1402-4896/acaad5
|View full text |Cite
|
Sign up to set email alerts
|

Research on surface roughness prediction in turning Inconel 718 based on Gaussian process regression

Abstract: Nickel-based alloy Inconel 718 is widely used in aircraft engine industry because of its good mechanical properties. Inconel 718 is a typical difficult-to-machine material and its price is relatively expensive. Therefore, accurate prediction of Inconel 718 machined surface roughness with small sample space can improve machining efficiency, optimize process parameters and reduce machining cost. In this paper, a method is proposed to characterize the influence of cutting parameters on roughness by stablishing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…Considering the strong dependence between contact state and interfacial leakage, a microporous structure consisting of composite rough and smooth surfaces in contact is used as a geometric model for interfacial leakage. A numerical technique based on the fast Fourier transform, widely used in mechanical engineering [40][41][42], is used to create the composite rough surface. The roughness of the surfaces is assumed to follow a Gaussian distribution [43].…”
Section: Numerical Reconstruction Of Interfacial Leakage Passagesmentioning
confidence: 99%
“…Considering the strong dependence between contact state and interfacial leakage, a microporous structure consisting of composite rough and smooth surfaces in contact is used as a geometric model for interfacial leakage. A numerical technique based on the fast Fourier transform, widely used in mechanical engineering [40][41][42], is used to create the composite rough surface. The roughness of the surfaces is assumed to follow a Gaussian distribution [43].…”
Section: Numerical Reconstruction Of Interfacial Leakage Passagesmentioning
confidence: 99%
“…The results achieved to demonstrate the effectiveness of three methods that have led to similar results represented by the optimal parameters. Hao et al [20] established a multi input single output (MISO) multivariate Gaussian process regression (GPR) surface roughness prediction model with cutting speed, depth of cut, feed and rake angle as input variables and surface roughness as output variable. The experimental results showed that the average relative error of MISO multivariate GPR surface roughness prediction model was 1.5%.…”
Section: Introductionmentioning
confidence: 99%